(untitled) (Journal of Atomic and Molecular Sciences, 2011)
A new number of inverse halogen bonds (IXBs) intermolecular interaction system of Y-F...DB_2 (D=C, N, O or S; B=O and S; Y=Cl) have been investigated at B3LYP/6-311++g(d, p) computational level. According to the BSSE corrected interaction energy, it can be concluded that the stability of the five IXBs complexes of the ClF...DB_2 system increases in the order of ClF...CS_2 < ClF...CO_2 < ClF...NO_2 < ClF...O_3 < ClF...SO_2. Comparing the ClF monomer with ClF moiety of the complexes, the chemical shifts of F atoms all increased by a certain degree and presented a trend to downfield. This indicates that the electrons flow from ClF to DB_2 (D=C, N, O or S; B=O or S) and the IXBs form between ClF and DB_2.